Gender, Raciality and Art Teaching: devices for dialogue - Rosa, Tatiana Gomes (Farol, 2024)
The excerpt presented for the conference with the same name as the title of this reflection, presented at the 15th Seminário Capixaba sobre o Ensino da Arte, is consistent with the issues that affect the time and space of research, as well as respect for the space of formative meetings and the trajectory that guide me towards the between black-woman-educator-teacher-artist-researcher with the teaching of art as a path of activism and reinvention-re-elaboration through curating as a path of healing in the doctoral process in the Postgraduate Program in Education, in the line of Cotidianos, Redes Educativas e Processos Culturais, at the Universidade do Estado do Rio de Janeiro.
Keywords: gender; ethnic-racial relations; art teaching